MANAJEMEN PROGRAM KHITAN MASSAL BERBASIS NILAI ISLAM: STUDI FENOMENOLOGI TENTANG DINAMIKA SOSIAL-BUDAYA MASYARAKAT PESISIR MALUKU - La Sugi; Salwa Salsabila Latua (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze how Islamic values-based management shapes the planning and implementation of a mass circumcision program in Werinama, Maluku, while also identifying the socio-cultural determinants that influence community participation. The research employed a qualitative approach with a phenomenological design. Data were collected through participant observation throughout the entire program cycle, semi-structured interviews with committee members, religious leaders, customary leaders, and parents, as well as a review of supporting documents. Data were analyzed using reflexive thematic analysis, while trustworthiness was ensured through source and technique triangulation, audit trails, and member checking. The findings reveal that community participation was influenced by three major determinants: political trust and perceptions of program politicization (42%), social prestige that frames circumcision as a symbol of status (28%), and expectations surrounding customary rituals (22%). From a managerial perspective, the program’s strengths were reflected in stakeholder mapping, clear task distribution, multi-channel communication, and post-procedure monitoring. However, a mismatch between program design and the ceremonial expectations of some families reduced social acceptance.